Technology Transfer Through Trade - Mombert Hoppe (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper examines the role that trade plays in economic development through the channel of technology transfer, approximated by total factor productivity. Three strains of factors influence the process of technology transfer; direct effort that is taken to transfer technologies, the capacity to adopt technologies, and differences in the underlying conditions between donor- and receiving countries. In this context, trade in (capital) goods allows technology import and improved input decisions. Second, trade opens export markets, allowing learning-by-doing. Third and most importantly, trade increases the set of accessible technologies, increasing the scope for imitation. The theoretical insights are compared to the empirical literature that deals with trade and technology transfer. Not surprisingly, it turns out that openness and human capital have a positive influence on the transfer of technology. Yet methodological problems with the data weaken the practical significance of the results, especially as the precise and fundamental mechanism of spillovers and the factors that condition the degree of technology transfer are not profoundly illuminated. These underlying processes have to be better understood in order to be able to give valuable policy recommendations that will go beyond the general advice of increasing openness and human capital formation.
Keywords: F10; F43; O40; 330; Technology transfer; Trade; Economic growth; Total factor productivity